Early pain detection and management after esophageal metal stent placement in incurable cancer patients: A prospective observational cohort study - Reijm, Agnes N.; Didden, Paul; Bruno, Marco J.; Spaander, Manon C.W. (Endoscopy International Open, 2016)
Background and study aims: Studies of esophageal self-expandable metal stents (SEMS) mainly focus on efficacy and recurrent dysphagia. Retrosternal pain has been described in up to 14 % of these patients, however, prospective daily pain assessment has not yet been performed. We conducted a prospective study to evaluate the occurrence and management of pain after esophageal SEMS deployment.Patients and methods: A total of 65 patients who underwent SEMS placement for incurable malignant esophageal stenosis were included. Patients used a diary to record intensity of pain twice daily for 2 weeks, according to the Numeric Rating Scale (NRS). A pain score ≥ 4 was used to determine whether patients experienced significant pain. If pain occurred, acetaminophen was used and, in cases of ongoing pain, an opiate was prescribed. Dose, duration, and kind of analgesic were noted.Results: The rate of significant pain increased from 0 % at baseline to 60 % on Day 1 (P < 0.001), followed by 37 % and 25 % on Days 7 and 14, respectively. The rate of analgesics use increased from 20 % at baseline to 78 % on Day 1 (P < 0.001), followed by 72 % and 62 % on Days 7 and 14, respectively. The use of opiates increased from 14 % at baseline to 42 % on Day 1 (P < 0.001). No variables associated with SEMS related pain were found. Conclusions: Two-thirds of patients experience significant pain after esophageal SEMS insertion and analgesics, including opiates, are frequently required. Patients need to be informed and preventive prescription of analgesia should be considered in order to improve quality of life.